RANCANG BANGUN APLIKASI PENGELOLAAN PEMESANAN TIKET PADA PO. PANCA SARI TOUR DAN TRAVEL SUMBAWA BERBASIS WEB - Miftahul Haq; Rodianto; Nur Yanuar Ansari (Hexagon Jurnal Teknik dan Sains, 2020)
This study aims to build a ticket booking management application that can help improve service and operator performance in serving ticket reservations at PO. Panca Sari Tour and Sumbawa Travel. The software development method used in this research is the prototype method. For tools in application design using Unified Modeling Language (UML) and applications are built using web-based programming languages. Research results have been submitted to PO. Panca Sari Tour and Sumbawa Travel to facilitate operators in monitoring departure schedules with the number of seats still available, searching passenger data, viewing booking details and updating passenger data so that ticket booking management can improve customer service performance.